Supervision Of The Financial Services Authority's (OJK) Strategy In Counteracting Illegal Investment In The Community - Komala Sridewi Lestari; Rani Apriani (Fakultas Hukum, Universitas Islam Bandung, 2022)
This study aims to find out the duties, functions, and authorities of the financial services authority and how the role of the financial services authority in supervising and preventing illegal investment fraud that is rife in the community. Using normative juridical research methods, investment in society in general is often known as investment. Another thing with illegal investment is business activities in the form of collecting funds from the community. Therefore, supervision of the financial services authority is needed to monitor and inform important information about good and correct investment requirements.